Phytoremediation, Antioxidant, Antimicrobial Activity of Callisia repens Silver Nanoparticles - Praneetha, Namamurali; Naidu, T Suchitra; Yadam, Sabitha (Asian Journal of Biological and Life Sciences)
The present work investigates the antioxidant, antibacterial, and photocatalytic properties of silver nanoparticles. At first, an apparent colour change was seen as proof that the AgNPs had been generated. The formation, size, and shape of the produced AgNPs were characterised using UV-vis spectroscopy and scanning electron microscopy. The existence of phytocompounds that were in charge of AgNP synthesis, bioreduction, stabilisation, and capping. The AgNPs’ and each leaf extract’s antioxidant potential was assessed using the TPC, FRAP, and phosphomolybdate tests. The antioxidant assay findings revealed that the AgNPs had higher antioxidant properties than the corresponding leaf extracts. In the TPC leaf, the extract showed greater activity than the respective AgNPs. Employing the well diffusion method in agar, the antimicrobial activity was performed on both bacterial and fungal strains. The photocatalytic activity of the synthesized nanoparticles was examined using the methylene blue degradation process. Green synthesized C. repens silver nanoparticles efficiently decreased the dye by approximately 68.77 percent at 72 hr after exposure.
Keywords: Antimicrobial activity; Antioxidant activity; Callisia repens; Methylene blue degradation; Silver nanoparticles